Synthetic Promoters in Gene Therapy: Design Approaches, Features and Applications - Valentin Artemyev; Anna Gubaeva; Anastasiia Iu. Paremskaia; Amina A. Dzhioeva; Andrei Deviatkin; Sofya G. Feoktistova; Olga Mityaeva; Pavel Yu. Volchkov (Cells)
Gene therapy is a promising approach to the treatment of various inherited diseases, but its development is complicated by a number of limitations of the natural promoters used. The currently used strong ubiquitous natural promoters do not allow for the specificity of expression, while natural tissue-specific promoters have lowactivity. These limitations of natural promoters can be addressed by creating new synthetic promoters that achieve high levels of tissue-specific target gene expression. This review discusses recent advances in the development of synthetic promoters that provide a more precise regulation of gene expression. Approaches to the design of synthetic promoters are reviewed, including manual design and bioinformatic methods using machine learning. Examples of successful applications of synthetic promoters in the therapy of hereditary diseases and cancer are presented, as well as prospects for their clinical use.